Conflict minerals in EU downstream companies’ CSR disclosures: A framework for analysis : A multiple-case study of consumer electronics and automotive companies - Väänänen, Elina (My University, 2022)
This study focused on ‘conflict minerals’, one of the emergent topics in corporate social responsibility (CSR). Conflict minerals refer to minerals and metals originating from conflict-affected or high-risk areas, where their illegal trade finances armed groups that commit serious human rights violations. The material scope of conflict minerals most commonly includes ‘3TG’, tin, tantalum, tungsten, gold, and their ores, which are crucial in many products familiar to consumers, such as cars, washing machines, and electronic household appliances. The EU Conflict Minerals Regulation (2017/821) and the non-binding guidelines addressing the EU Non-Financial Reporting Directive (2014/95) recommend that EU downstream companies address conflict minerals in their CSR disclosures. This thesis aimed to present a framework for analyzing EU downstream companies’ conflict mineral disclosures. It also examined how large EU downstream companies in the consumer electronics and automotive industries manage the conflict minerals issue in their CSR reports. The framework for analysis is based on a literature review of CSR and responsible sourcing concepts, the issue of conflict minerals, and existing legislative acts and guidelines for responsible sourcing of minerals. As a result of the literature review, 19 key components were identified as relevant for EU downstream companies’ reporting on conflict minerals. The key components were categorized under five key elements: company strategy and internal management systems, supplier engagement, risk assessment and management, collaboration, and performance tracking. As part of the framework for analysis, a maturity model was developed based on the identified key components. This thesis empirically investigated the disclosures of eight large EU-based companies in two downstream industries known to consume 3TG: the automotive and consumer electronics industry. A qualitative multiple case study research approach and a content analysis method were used to obtain the objective. The research data comprised annual CSR disclosures regarding the year 2018 and other CSR disclosures published in document format on case companies’ websites. The conclusions of this thesis present the main findings and propositions for further research. The results show that even though no EU legislation obliges EU downstream companies to report on conflict minerals, most of the case companies in the automotive and consumer electronics have addressed the issue in their CSR disclosures. In addition, the results show that there are no evident differences in disclosure maturities when comparing the two industries. Common for the two case industries was that companies in both industries seem to use monitoring as their primary supplier engagement strategy, and collaborate cross-industry to engage with the smelters and refiners. In addition, their CSR reports lack communication on key performance indicators and future targets regarding responsible mineral sourcing. Differences were found in how companies engage with their suppliers, report on the smelters and refiners in their supply chains, collaborate with other industry peers, and track their performance related to conflict minerals.

Tämä tutkielma keskittyi “konfliktimineraaleihin”, joka on yksi viime aikoina esillä olleista aiheista yritysvastuuta koskevassa keskustelussa. Käsite viittaa konfliktialueilta ja korkean riskin alueilta peräisin oleviin mineraaleihin ja metalleihin, joiden kaupan katsotaan rahoittavan aseellisia ryhmittymiä ja olevan yhteydessä vakaviin ihmisoikeusloukkauksiin. Konfliktimineraaleiksi luetaan yleensä tina, tantaali, volframi, niiden malmit sekä kulta, joita käytetään monissa kuluttajillekin tutuissa tuotteissa, kuten autoissa, pesukoneissa ja kodin pienelektroniikassa. Euroopan unionin konfliktimineraaliasetus 2017/821 sekä EU:n antamat suositukset muuta kuin taloudellista raportointia koskevalle direktiiville 2014/95 kehottavat EU-alueen tuotantoketjun loppupään yrityksiä sisällyttämään konfliktimineraalit osaksi vastuullisuusraportointiaan. Tämän tutkielman tavoitteena oli muodostaa teoreettinen viitekehys, jonka avulla EU-alueen tuotantoketjun loppupään yritysten yritysvastuuraportteja voidaan analysoida konfliktimineraalien näkökulmasta. Lisäksi tutkielmassa tarkasteltiin, miten suuret auto- ja kuluttajaelektroniikkayritykset EU:ssa raportoivat konfliktimineraaleista yritysvastuu-raporteissaan. Teoreettinen viitekehys perustuu kirjallisuuskatsaukseen, jossa paneuduttiin yritysvastuun ja vastuullisen hankinnan käsitteisiin, konfliktimineraaleihin sekä olemassaoleviin lainsäädännöllisiin toimiin ja toimintaohjeisiin, jotka koskevat EU-yrityksiä. Kirjallisuuskatsauksen tuloksena tunnistettiin 19 osatekijää, jotka ovat oleellisia EU-yritysten konfliktimineraaleja koskevissa yritysvastuujulkaisuissa. Nämä 19 osatekijää ryhmiteltiin viiteen kategoriaan: yrityksen strategia ja hallintojärjestelmät, toimittajien sitouttaminen, riskien tunnistaminen ja niiden hallinta, yhteistyö sekä suoriutumisen seuranta. Osana viitekehystä kehitettiin myös maturiteettimalli, joka perustuu edellämainittuihin osatekijöihin ja kategorioihin. Tutkielmassa analysoitiin kahdeksan suuren EU-yrityksen yritysvastuuraportteja. Neljä tutkimuskohteiksi valituista yrityksistä valmistaa autoja ja toiset neljä ovat kuluttajaelektroniikan valmistajia. Tutkimus toteutettiin laadullisena monitapaustutkimuksena käyttäen sisällönanalyysiä aineiston analyysitapana. Tutkimusaineisto käsitti tapausyritysten vuosittain julkaistavia yritysvastuuraportteja, jotka koskevat vuotta 2018. Osana tutkimusaineistoa oli lisäksi muita yritysten verkkosivuilta löytyneitä yritysvastuujulkaisuja. Tutkielman johtopäätöksissä esitellään tärkeimmät tulokset sekä propositiot. Tulokset osoittavat, että vaikka tuotantoketjun loppupäässä sijaitsevia EU-yrityksiä ei EU-sääntelyn puitteissa velvoiteta raportoimaan konfliktimineraaleihin liittyen, useimmat tapausyrityksistä ovat käsitelleet aihetta yritysvastuuraportoinnissaan. Kahta toimialaa vertailtaessa ilmeistä eroa raportoinnin maturiteeteissa ei ilmennyt. Yhteistä toimialoille oli muun muassa se, että kummankin toimialan yritykset käyttävät monitorointia pääasiallisena strategianaan toimittajiensa sitouttamisessa sekä tekevät yhteistyötä muiden toimialojen kanssa tavoittaakseen sulatot ja jalostamot toimitusketjuissaan. Eroja toimialojen välillä ilmeni muun muassa siinä, miten yritykset sitouttavat toimittajiaan, tekevät yhteistyötä muiden toimijoiden kanssa ja seuraavat suoriutumistaan.
Keywords: conflict minerals, CSR reporting, responsible sourcing